Peran Etika Bisnis dalam Peningkatan E-WOM, E-Trust dan E-Satisfaction untuk Meningkatkan Repurchase Intention - Mahirun; Arih Jannati; Wenty Ayu Sunarjo (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
This study aims to test and analyze the factors that influence repurchase intention involving the variables of electronic word of mouth (e-WOM), e-trust, and e-satisfaction. The object of this research is students in Indonesia who have made transactions in the shopee marketplace. Multiple linear regression is the analytical technique used to test the effect of independent variables on the dependent variable. After 203 samples were tested, it was found that e-satisfaction had a positive and significant impact. Meanwhile, e-WOM and e-trust has a positive and insignificant influence.